Performance of the 2023 diagnostic criteria for MOGAD: real-world application in a Chinese multicenter cohort of pediatric and adult patients - Meng-Ting Cai; Yi Hua; Qi-Lun Lai; Sheng-Yao Su; Chun-Hong Shen; Song Qiao; Yong-Feng Xu; Zhe-Feng Yuan; Yin-Xi Zhang (BMC Medicine)
Abstract Background The clinical phenotypes of myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) have been found to overlap with several other diseases. The new criteria proposed in 2023 were designed to better identify the disease but require validation across various populations to ascertain its clinical utility. We aimed to investigate the diagnostic performance in phenotypically diverse patients. Methods This multicenter study retrospectively included adult and pediatric patients who were hospitalized for a first suspected demyelinating event and tested positive for MOG immunoglobulin G (IgG) during the acute phase. The 2023 Lancet Neurology criteria were assessed against the benchmark of empirical clinical diagnosis, and the 2018 JAMA Neurology and Journal of Neuroinflammation criteria were also evaluated for comparative analysis. Results Among the 291 eligible patients (82 adults, 209 children), 282 (96.9%) were clinically diagnosed as definite MOGAD (77 adults, 205 children), while 262 (90.0%) fulfilled the 2023 diagnostic criteria (78 adults, 184 children). A total of 265 patients met the criteria for core clinical demyelinating events, and 76 (26.1%) had serum clear positive MOG-IgG (≥ 1:100). The sensitivity of the 2023 criteria was 0.91 (adults vs. children = 0.97 vs. 0.89), the specificity was 0.56 (adults vs. children = 0.40 vs. 0.75), positive likelihood ratio was 2.06 (adults vs. children = 1.62 vs. 3.57), and negative likelihood ratio (NLR) was 0.15 (adults vs. children = 0.06 vs. 0.14). Additionally, 264 and 256 cases were classified as definite MOGAD by the 2018 JAMA Neurology and Journal of Neuroinflammation criteria, respectively. Compared to the 2023 diagnostic criteria, the 2018 JAMA Neurology criteria demonstrated similar diagnostic performance. However, the 2018 Journal of Neuroinflammation criteria exhibited comparable sensitivity (0.92, adults vs. children = 0.96 vs. 0.89), higher specificity (1.00, adults vs. children = 1.00 vs. 1.00) and better NLR (0.09, adults vs. children = 0.04 vs. 0.11). Conclusions The 2023 criteria demonstrated good sensitivity in adult and pediatric patients in China yet modest specificity. Close follow-up is needed for patients with atypical phenotypes but high-titer MOG-IgG to avoid underdiagnosis.